Apoptosis is one cause of thrombocytopenia in patients with high-altitude polycythemia. (31st December 2023) - Wang, Zhuoya; Tenzing, Noryung; Xu, Qiying; Liu, Huifang; Ye, Yi; Wen, Yi; Wuren, Tana; Cui, Sen
Abstract: High-altitude polycythemia (HAPC) can occur in individuals who are intolerant to high-altitude hypoxia. In patients with HAPC, erythrocytosis is often accompanied by a decrease in platelet count. Chronic hypoxia can increase the incidence of arteriovenous thrombosis and the risk of bleeding during antithrombotic treatment due to thrombocytopenia; therefore, understanding the cause of thrombocytopenia can reduce the risk of treatment-related bleeding. In this study, we examined platelet production and apoptosis to understand the cause of thrombocytopenia in patients with HAPC. The classification of myeloid-derived megakaryocytes (MKs) in HAPC patients was mainly granular MKs rather than mature MKs, suggesting impaired differentiation and maturation. However, the total number of MKs and newly generated reticulated platelets in the peripheral blood increased, indicating sufficient platelet generation in HAPC thrombocytopenia. Increased platelet apoptosis may be one of the causes of thrombocytopenia. Platelet activation and GP1bα pathway activation induced by thrombin and von Willebrand factor can lead to platelet apoptosis. Platelet production was not reduced in patients with HAPC, whereas platelet apoptosis was associated with thrombocytopenia. These findings provide a rationale for considering the bleeding risk in HAPC patient while treating thrombotic diseases. Plain Language Summary: What is the context? Platelets are essential in the process of blood clotting; hence, low platelet count increases the risk of bleeding. Thrombocytopenia is present in patients with high-altitude polycythemia Hypoxia can lead to platelet activation and increase in procoagulant factors, while at the same time increase the risk of thrombosis due to erythrocytosis and blood stasis. Antithrombotic therapy should be administered when thrombosis occurs in patients with high altitude polycythemia; however, due to the low platelet count, risk of bleeding must be considered. What is new? In this study, we found that platelet production was not decreased in patients with high-altitude polycythemia. One cause of thrombocytopenia is apoptosis, which is associated with platelet activation, especially GP1bα activation. Inhibition of GP1bα binding to ligand decreased the level of platelet apoptosis. What is the impact? This study provides novel insights into antithrombotic therapy for patients with high-altitude polycythemia complicated by thrombosis. Thrombocytopenia is associated with excessive apoptosis. Interfering with GP1bα targets may have a dual benefit, both in inhibiting thrombosis and avoiding thrombocytopenia.